PENGARUH PENGGANTIAN SEBAGIAN SEMEN DENGAN ABU TERBANG (FLY ASH) DAN ABU CANGKANG LOKAN TERHADAP KUAT TEKAN PAVING BLOCK - Marwan, Marwan; Supriani, Fepy; Afrizal, Yuzuar (Inersia: Jurnal Teknik Sipil, 2017)
Paving block is used to fill the needs of surface pavement. This research uses waste of sea shell ash and fly ash as cement substitute material in the manufacture of paving blocks. Sea shell ash and fly ash containing calcium oxide (CaO) and silica oxide (SiO) that can replace and strengthen the chemical composition of cement. Variations of replacement much as 2.5%, 5%, 7.5% and 10% compared to normal compressive strength of the paving block (0%). Test specimen numbered 75 samples of rectangular with a length of 20 cm, width 10 cm and a thickness of 6 cm. Manufacture of paving blocks using conventional construction methods. The results of compressive strength testing of the age of 7 days, 14 days and 28 days for any 2 variations on the variations increase to 7.5% and down 10%. The results of the compressive strength largest average variation occurs in the replacement of 7.5% ie at the age of 7 days of 31.19 MPa, aged 14 days amounted to 33.55 MPa and 28 days amounted to 34.74 MPa. The percentage increase was highest compressive strength at 28 days with an increase of 23.19%.